Evaluating the Risk Assessment Approach of the REACH Legislation: A Case Study. Issue 1 (29th October 2018) - Landberg, Hanna E; Hedmer, Maria; Westberg, Håkan; Tinnerberg, Håkan
Abstract: Risk assessments based on occupational exposure to chemicals have increased since REACH (European regulation on Registration, Evaluation, Authorization, and restriction of Chemicals) came into force. The European Chemicals Agency (ECHA) recommends that chemical exposure could be calculated using exposure models and that parameters used to calculate the exposure scenario (ES) should be communicated in extended safety data sheets (e-SDS) as workplace instructions which downstream users are obligated to follow. We aimed to evaluate REACH's risk assessment approach using the Stoffenmanager ® 6.1, the Advanced REACH Tool 1.5 (ART), and the European Centre for Ecotoxicology and Toxicology of Chemicals' targeted risk assessment (ECETOC TRA 3.1) exposure models. We observed 239 scenarios in three companies handling chemicals using 45 e-SDS. Risk characterization ratios (RCRs) were calculated by dividing estimated exposures by derived no-effect levels (DNELs). Observed RCRs were much lower than registered RCRs, indicating lower exposures. However, about 12% of the observed ES still had RCRs > 1, after adjustment for control measures and personal protections described in the ES, when using Stoffenmanager ® . The ES with observed RCRs > 1 were the same by Stoffenmanager ® and ART, but not by ECETOC TRA. Stoffenmanager and ART identified 25 adjusted scenarios with RCR > 1, while ECETOC TRA gave RCR < 1 for the same scenarios. The ES with RCR > 1 were significantly associated to chemicals with higher vapour pressure and lower DNELs than ES with RCR < 1 by Stoffenmanager ® . The correlations between observed and registered RCRs were lower than those between RCRs calculated from the different models themselves; ECETOC TRA had the lowest correlation with the registered ES. These results put in question the generic ES recommended under the REACH legislation. Downstream users may get better estimates by assessing their own ES, especially for chemicals with low DNELs and high vapour pressure.